Electric field analysis of different electrode systems used for breakdown tests of insulating liquids with FEM - Taslak, Eyup; Kalenderli, Ozcan (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2018)
Solid, liquid, gas and composite insulators are utilized for power system equipment insulation. In HV power transformers, insulating liquids are used to provide both electrical insulation and cooling the transformer. The electrical stress on insulating liquid depends on many factors such as applied voltage, electrode geometry, and foreign particles. In this regard, analysis of electric field changes occurring due to gas bubbles and water droplets between the different electrodes, and determination of the critical breakdown area are important for effective use of insulating liquid. In this study, effects of VDE and disk electrode systems on the breakdown voltage of mineral oil at different rates of voltage rise are examined theoretically and experimentally. In addition, the electrical stresses in the oil with and without air bubbles and water droplets are investigated with FEMM program using finite element method (FEM). The examined electrode systems are modeled as 2D using axial symmetry. In this approach, it is considered that 3D electric field distribution is obtained by rotating 2 pi radians around the symmetry axis of the models. Analysis results show that the VDE electrode system has lower electric field strength in the oil than the disk electrode system, thus it provides higher breakdown voltage.
Keywords: High voltage; insulating oil; breakdown strength; electric field analysis; finite element method; VOLTAGE; OIL; Engineering